Spectral detection of graphene and graphene oxide with SU-8 based asymmetry tripled-Arm Mach Zehnder - Amiri, Iraj Sadegh; Ariannejad, Mohammad Mahdi; Abdullah, Hewa Yaseen; Yupapin, Preecha Promphan (Elsevier, 2018)
This paper reports the experimental application of the fabricated SU-8 based triple arm Mach-Zehnder interferometer (MZI) in the detection of graphene and graphene oxide. A standard MZI has two arms in its structure. In our design, we combine two MZIs with different dimensions together in a way that a short arm MZI replaces one longer arm of the larger MZI. The parallel connections of the two MZIs with a common arm would enhance the overall sensitivity of the sensor. The measurands graphene and graphene oxide with almost similar refractivity has been applied to sensing arms of the MZI in separate steps. The equidistance picometric spectral shifts corresponding to each measurands over the operating wavelength of 1550 nm are observed and is suitable for detection of graphene and graphene oxide.